Experiência do tempo: reflexões acerca da temporalidade histórica na escrita ensaística de Bertrand Russell - Ferreira dos Reis, Marlon (Temporalidades, 2019)
Since François Hartog, in his work, Regimes of historicity, expressed the analysisof experiences of time, a lot has evolved on the discussion about its limits and possibilities inthis model of historical interpretation. Hence, what I propose in this paper is a reflection onthe subject of the identity construction on the experimentation of periods. Therefore, I willwork with the British philosopher Bertrand Russell’s (1872-1970) essays, ordered in thecollection Portraits from memory & other essays, aiming to demonstrate how historical timeis deeply knit with subjective time, ordered by the narrative. The reflections disposed herewill be divided into three moments: (1) the brief explanation on the period of historical crisethat Cold War was, (2) how this context of tension is used by Russell to build his identity,and, finally, (3) the relationship between essay writing, in its narrative aspect, and theelaboration of human temporality. Ending with the dissociation of the self with its contextsin experiences of time.